What affects farmers in choosing better agroforestry practice as a strategy of climate change adaptation? An experience from the mid-hills of Nepal. Issue 6 (June 2022) - Paudel, Deepa; Tiwari, Krishna Raj; Raut, Nani; Bajracharya, Roshan Man; Bhattarai, Suman; Sitaula, Bishal K.; Thapa, Shivaraj
Abstract: Determinants for choosing climate change adaptation strategies and selecting improved agroforestry practices have rarely been explored, while numerous studies have been conducted on climate change and agroforestry. This paper discusses; local understanding of climate change, climatic impacts, and factors that affect farmers' choices of adaptation strategies, and agroforestry practices. We focused on three districts located in the mid-hills of Nepal, where farmers were adopting agroforestry practices in two forms; traditional and improved practices. We followed three techniques of social survey; household survey (n = 420), focus group discussions (n = 6), and key informant interviews (n = 24). Almost all farmers of the study areas were experiencing climatic challenges, but only 59.29% of them accepted that the challenges are induced by climate change and, likewise, 55.24% have adopted climate change adaptation measures. Diversifying crop production, shifting farming practices, changing occupation, and emigration were local adaptation strategies. Livelihood improvement, income generation, and food production were the primary motives for adopting agroforestry practices in the study area. Agroforestry as an adaptation measure to climate change was considered secondary by most farmers. Statistical analysis using a logit model revealed that age, education, and habit of growing commercial species significantly influenced farmers adopting climate change adaptation strategies. Likewise, age, education, gender, habit of growing commercial species, and income from tree products significantly influenced the choice of improved agroforestry practices as a better option. Though agroforestry was widely considered a strategy to combat climate change, only some farmers accepted it due to their awareness level. Therefore, education programs such as training, farmer field schools, door-to-door visits, etc., should be intensified to sensitize farmers about climate change and encourage them to adopt improved agroforestry practices. The findings of the study could reinforce local, national, and international allied agencies to design operative actions in the days to come. Highlights: Modification of the traditional agroforestry practice to optimize household benefits. Out of total farmers experiencing climatic effects, only some of them were adopting adaptation strategies. Multiple factors affect farmers in adopting climate change adaptation strategies. Multiple factors affect farmers for selecting the better agroforestry practice. Additional education programs are required to promote the agroforestry practice. Abstract : Income; Climatic effects; Traditional practice; Improved practice; Education; Combat.